Transfusion Camp: The UK experience and its value in improving knowledge of transfusion medicine among postgraduate trainees - Aggarwal, A; Kaushik, K; Morton, S; Danaee, A; Gurung, K; Robinson, S; Kapitany, C; Charge, S; Lin, Y; Desborough, M; Murphy, MF (Wiley, 2024)
Objectives: To report the UK experience of rolling out Transfusion Camp. Background: Transfusion Camp is a structured education programme developed in Toronto, with the aim of reducing knowledge gaps in transfusion medicine in postgraduate trainees. It consists of didactic lectures viewed online by the participants, then interactive, locally delivered seminars. Since 2015, it has been rolled out in the United Kingdom, and is now available in four centres. Here, we report the UK experience of Transfusion Camp and outcomes. Methods: Trainees are recruited via the training programme directors in each region. Pre‐ and post‐course assessments are administered using the validated BEST (Biomedical Excellence for Safer Transfusion) test, with possible scores 0–20, and confidence measured on an A‐E Likert scale. Results: Since 2015, 130 trainees have participated in Transfusion Camp in the United Kingdom. Trainees from all specialties significantly improved their BEST‐test scores after attending the course (mean score 11.6/20 before the course, compared with 14.3/20 after the course), and confidence in managing transfusion‐related issues was also significantly improved. Conclusion: We recommend that all centres consider offering Transfusion Camp to trainees in haematology and other specialties that frequently use blood transfusions, such as anaesthesia/ICU, Internal Medicine and others.